Analisis Pengaruh Promosi Penjualan, Kualitas Layanan, dan Pengalaman Pelanggan terhadap Loyalitas Konsumen Pengguna GoFood: Studi pada Mahasiswa Prodi Kewirausahaan UNIMED - Liston Rivaldo Sitorus; Rangga Restu Prayogo (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to examine and understand the extent to which Promosi Penjualan, Kualitas Layanan, and Pengalaman Pelanggan influence Consumer Loyalty among GoFood service users, particularly among students of the Entrepreneurship Study Program at Medan State University, intakes of 2021 to 2024. The method used in this study is a quantitative approach with an associative research type. The research sample consisted of 120 respondents selected through a purposive sampling technique. Data collection was carried out using a Likert-scale questionnaire. The results of the study indicate that Promosi Penjualan has a positive and significant influence on Consumer Loyalty. Similarly, Kualitas Layanan and Pengalaman Pelanggan also have a positive and significant influence on Consumer Loyalty. Together, these three variables are proven to have a significant influence on increasing Consumer Loyalty to GoFood services.